Experience report: An extension project on good health practices in primary care - Santiago, Ruan Braga; Moura, Lucas Eliel Beserra; Reis, Victoria Melo; Aguiar, Roma Victor Olegário; Dantas, Raíssa Soares; Rodrigues, Renata Viana; Neto, Rodolfo Basilio Madeira; Nogueira, Pedro Brito; Lima, Amanda Almeida; Picanço, Nicole Mota (Seven Editora, 2023)
The concept of primary health care (PHC) is fundamental for the promotion of well-being and disease prevention, although it has been reinterpreted over the years. A clear definition was developed to facilitate its implementation, highlighting PHC as a comprehensive health approach that meets people’s needs, from health promotion to palliative care, close to the everyday environment. Principles such as universality, equity and integrality guide PHC, ensuring access to all, respect for diversity and comprehensive care (BRASIL, 2010, 2021). DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-176